(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This text is a theoretical essay that starts from concerns about the video performance All about that bass produced by the artist Royce Cherdan Lee, also known as Chubbeyoncé Lee. The video performance was inspired by the original music video of the same title, by the American singer Meghan Trainor. It aims to reflect on issues related to space, body and affection as dramaturgical dimensions in audiovisual productions posted on the YouTube digital platform, based on concepts such as: Exotopy; Heterotopia; Space Dramaturgy; Corpomidia and Spreadable Media; to expose understanding of knowledge, subjectivities and the scenic and social interventions related to that video performance to create an evocative nature of text that is metonymic, subjective, nervous and citatory. For such purposes, Performative Writing is used as a mode to perform writing. In All about that bass the backyard, the bodies that inhabit it and the affection that generate actions are the points of interest of this essay.